Climate Constitutionalism in Indonesia: Legal Pathways for Climate Action - Amir, Irfan; Try Setyawanta , Lazarus; Diamantiana , Amalia; Sugirman, Andi (Al-Bayyinah, 2025)
Climate change constitutes a multidimensional environmental and constitutional challenge that demands coherent legal frameworks capable of guiding state responsibility in mitigation and adaptation efforts. This study examines Indonesia’s climate governance through the lens of climate constitutionalism, focusing on how constitutional norms, legal institutions, and policy structures shape the state’s climate obligations. Employing a normative-empirical approach, the research analyzes constitutional provisions, statutory regulations, judicial decisions, and international climate agreements, complemented by institutional reports and selected case studies. The findings reveal that although Indonesia’s Constitution recognizes the right to a good and healthy environment, fragmented legal frameworks, institutional layering, and weak inter-sectoral coordination undermine the effective realization of substantive climate rights. The absence of an explicit constitutional interpretation linking climate obligations to fundamental environmental rights further limits state accountability and constrains the integration of intergenerational and ecological justice into national policy. This study argues that strengthening climate governance does not require a formal constitutional amendment but rather a reinterpretation of constitutional duties through the lens of climate justice. By articulating climate constitutionalism as a normative and institutional pathway, this research contributes to the broader discourse on constitutional environmentalism and offers a context-sensitive model for Global South countries seeking to align domestic legal systems with climate imperatives. Future reforms should prioritize institutional coherence, enhanced judicial engagement, and meaningful public participation to ensure that constitutional environmental commitments translate into enforceable and measurable climate action.